Apakah QRIS Benar-benar Meningkatkan Kinerja UMKM? Sebuah Studi Eksplanatori Sekuensial Berbasis TAM di Lampung, Indonesia - Masthuroh, Masthuroh; Sari, Asia Novita; Indriyani, Indriyani (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2025)
The increasing competitiveness and performance of micro, small, and medium enterprises (MSMEs) is significantly driven by the digital payment transformation towards the Quick Response Code Indonesian Standard (QRIS). However, there is still limited empirical evidence on how the Technology Acceptance Model (TAM) components and social influence shape QRIS usage and its impact on MSMEs performance. The purpose of this study is to examine how people's perceptions of usefulness, ease, convenience, trust, and social influence QRIS adoption. Furthermore, this study will also investigate how QRIS adoption impacts MSMEs performance in Lampung Province. This study was conducted using a mixed-methods, sequential explanatory design. The quantitative phase involved 198 small and medium enterprises (MSMEs) using QRIS, selected using a purposive-snowball sampling technique. After financial reports and questionnaires were collected, PLS-SEM was used to analyze the data. To enhance and explain the quantitative findings, a qualitative process was conducted through in-depth interviews. The results showed that perceived usefulness, ease, and trust had a positive and significant influence on QRIS usage. Perceived convenience and social influence, on the other hand, did not. It has been proven that the use of QRIS improves MSMEs performance by increasing transaction volume, sales, profits, and operational cost efficiency. The results indicate that improving digital literacy and system security elements are crucial to driving better QRIS adoption among MSMEs.